Prevalence of hypertension and its association with dietary practices in a rural area of Ranchi district of Jharkhand - Kumar, Chandramani; Haider, Shamim; Kashyap, Vivek (Indian Journal of Community Health, 2014)
Background: Hypertension is a major public health problem affecting people across the globe. Rapid change in life style and dietary practices are important factors for increasing prevalence of hypertension. High salt consumption, fat intake and low consumption of dietary fibres are important modifiable risk factors of hypertension. Aims & Objectives: 1) To determine the prevalence of hypertension in community under study. 2) To describe the association of dietary practices and hypertension in community. Materials and Methods: A descriptive cross sectional study in one of the rural field practice area (Ormanjhi) of RIMS, Ranchi was done. Sample size was determined using nMaster 2.0 software. Total 500 people were included in the study. Cluster sampling method was adopted to draw the sample. Subjects 20 years and above from both sex were eligible for the study. Pre-tested semi structured questionnaire were used for data collection. Template was generated in MS excel and data analysis was done using SPSS 13 software. Results: Prevalence of hypertension in the present study was found to be 19.8%. Mean systolic and diastolic blood pressure was found to be 122.83 mm of Hg (SD – 15.83) and 79.24 mm of Hg (SD - 8.73) respectively. Prevalence of hypertension was higher among male (22.8%) than female (16.5%) although this difference was statistically not significant (p – value = 0.075). Prevalence of hypertension was more among non-vegetarians (23.9%) compared to vegetarians (8.3%). Added salt intake was found to be significantly associated with hypertension (p - value = 0.023). Conclusions: Prevalence of hypertension was more among male population. Higher prevalence of hypertension was found among subjects with non-vegetarian diet and high salt in their diet.